Controls on Rift Faulting in the North Basin of the Malawi (Nyasa) Rift, East Africa - Shillington, Donna J.; Scholz, Christopher A.; Chindandali, Patrick R. N.; Gaherty, James B.; Accardo, Natalie J.; Onyango, Evans; Ebinger, Cynthia J.; Nyblade, Andrew A. (Tectonics (Washington, D.C.), 2020)
The North Basin of the Malawi Rift is an active, early‐stage rift segment that provides the opportunity to quantify cumulative and recent faulting patterns in a young rift, assess contributions of intrarift faults to accommodating rift opening, and examine controls on spatial patterns of faulting. Multichannel seismic reflection data acquired in Lake Malawi (Nyasa) in 2015 together with legacy multichannel seismic data image a system of synthetic intrarift faults within this border‐fault‐bounded, half‐graben basin. A dense wide‐angle seismic reflection/refraction dip profile acquired with lake bottom seismometer data constrains sediment velocities that are used to convert fault throws from travel time to depth. Observed extension on intrarift faulting in the northern and central parts of the North Basin is approximately twice what would be predicted for hanging wall flexure, implying that the intrarift faults contribute to basin opening. The cumulative throw on intrarift faults is higher in the northern part of the rift segment than the south and is anticorrelated with throw on the border fault, which is largest in the southern part of the North Basin. This change in faulting coincides with a change in the orientation of the North Basin from a N‐S trend in the south to a NNW‐SSE trend in the north. We infer that the distribution of extension is influenced by rift orientation with respect to the regional extension direction. Almost all intrarift faults substantially offset late Quaternary synrift sediments, suggesting they are likely active and need to be considered in hazard assessments. Key Points Intrarift faulting contributes to rift opening The style and amount of rift faulting change along strike in North Basin Nearly all intrarift faults have been active in the last ~75 kyr